(untitled) (TSUL LEGAL REPORT, 2026)
This article examines the features of mitigating circumstances when imposing punishment and the issue of taking into account in the presence of special (special) rules for mitigating circumstances. The role and significance of the general principles of sentencing and the principle of imposing punishment in the appointment of punishments were have analyzed. At the same time, this article analyzes the practical significance of the circumstances mitigating punishment when imposing punishment by studying some of the circumstances mitigating punishment. Also, about the active repentance of the perpetrator of the deed, various and similar features of punishment with the appointment of a lighter punishment, as well as some theoretical and practical problems associated with their application in the appointment of punishment. In addition, this article discusses the features of extenuating circumstances sentencing and the issue of their consideration in the presence of special rules of mitigating circumstances. This article describes the specific features of sentencing with active repentance of the offender, various and similar features of punishment with the imposition of a milder punishment, as well as some theoretical and practical problems associated using them in sentencing. As a result of this article relevant recommendations have been developed and proposals for improving the criminal law of the Republic of Uzbekistan.